Reflectance Confocal Microscopy of Aging Skin and Skin Cancer - Stefania Guida; Giovanni Pellacani; Silvana Ciardo; Caterina Longo (Mattioli1885, 2021)
Skin aging is a complex process that causes morphologic variations. Some of these variations have been hypothesized to be involved in skin cancer development. This paper reviews current knowledge of the features of aged skin as seen with reflectance confocal microscopy (RCM). Basic principles of the technique are described, and the RCM features of healthy skin and skin cancer are briefly discussed. Moreover, the RCM features at different layers of young and elderly skin are described, as are the variations that occur with passing years and in relation to sun exposure that contribute to photoaging and the development of skin cancer. RCM enables the noninvasive evaluation, at quasi-histologic resolution, of aging-related skin changes, some of which are shared with skin cancer; this ability helps avoid skin biopsy. Further research is needed to understand the relation between skin aging and skin cancer development.